Measurement of the ratio of the p over(p, ̄) → W + c-jet cross section to the inclusive p over(p, ̄) → W + jets cross section - Abazov, V; Abbott, B; Abolins, M; Acharya, B; Adams, M; Adams, T; Aguilo, E; Ahn, S; Ahsan, M; Alexeev, G; Alkhazov, G; Alton, A; et al. (2008)
We present a measurement of the fraction of inclusive W + jets events produced with net charm quantum number ±1, denoted W + c-jet, in p over(p, ̄) collisions at sqrt(s) = 1.96 TeV using approximately 1 fb-1 of data collected by the DØ detector at the Fermilab Tevatron Collider. We identify the W + jets events via the leptonic W boson decays. Candidate W + c-jet events are selected by requiring a jet containing a muon in association with a reconstructed W boson and exploiting the charge correlation between this muon and W boson decay lepton to perform a nearly model-independent background subtraction. We measure the fraction of W + c-jet events in the inclusive W + jets sample for jet pT > 20 GeV and pseudorapidity | η | < 2.5 to be 0.074 ± 0.019 (stat .) ±0.0140.012 (syst .), in agreement with theoretical predictions. The probability that background fluctuations could produce the observed fraction of W + c-jet events is estimated to be 2.5 × 10-4, which corresponds to a 3.5σ statistical significance.